Inovasi Arsitektur Amfibi dan Rekayasa Lanskap Adaptif untuk Ketahanan Permukiman terhadap Banjir di Bantaran Sungai Tuweley, Tolitoli - Purnomo, Dwi; Ahmad, Fandi (Tolis Ilmiah : Jurnal Penelitian, 2025)
The increasing risk of flooding in settlements along the Tuweley River, Tolitoli, driven by climate change and environmental degradation, has resulted in more frequent and intense flood events. These conditions have caused significant infrastructure damage, reduced living standards, and substantial socio-economic losses. Addressing this challenge requires integrated solutions that combine flood control measures with interconnected drainage systems and building designs capable of adapting to inundation. This study aims to develop concepts of amphibious architecture and adaptive landscape engineering to enhance regional resilience. Amphibious architecture enables structures to adjust dynamically to fluctuating water levels through flexible design systems. At the same time, adaptive landscape engineering applies ecological principles to mitigate flood impacts and improve water infiltration capacity. The research methodology consists of three main stages: (1) vulnerability assessment using GIS mapping and HEC-RAS simulations, (2) participatory design processes involving local communities through focus group discussions (FGDs) to incorporate indigenous knowledge and practical needs, and (3) small-scale prototype testing to evaluate the performance of proposed solutions. Anticipated outcomes include an amphibious architectural model, nature-based landscape strategies, and policy recommendations for local authorities. Implementation will be pursued through Memorandums of Understanding (MoUs) with key stakeholders, supported by follow-up FGDs to develop strategies for collaboratively creating safer, more resilient, and sustainable settlements.